ORGANIZACJA JEDNOŚCI AFRYKAŃSKIEJ W PROCESIE POKOJOWEGO REGULOWANIA SPORÓW MIĘDZYNARODOWYCH W AFRYCE - Sidi Diallo, Boubacar (Wydział Prawa i Administracji UAM, 1999)
The Author discusses the genesis o f the Organization o f African Unity, its aims and operational principles as well as, next, its structure and regulations on membership. Then the nature of international litigation in African continent and the role of the Organization in its settlement (against general historical background) are presented. Finally, the practice of African States in the process of settlement of international litigation as well as the contribution of the OAU to this process are discussed - with a series of concrete examples of such conflicts. 20 T.
THE ORGANIZATION OF AFRICAN UNITY IN THE PROCESS OF PEACEFUL SETTLEMENT OF INTERNATIONAL LITIGATION IN AFRICA